Керамічні печі з Борисфена середини VI ст. до н. е. - Крутілов, В.В. (Археологія, 2015)
Статтю присвячено сучасним археологічним дослідженням на о. Березань (давній Борисфен) архаїчного часу. На ділянці ГШ уперше за історію дослідження поселення було відкрито гончарний район середини VI ст. до н. е. з випалювальними керамічними печами. Деякі печі були зруйновані під час виробничого процесу та містили залишки місцевої керамічної продукції. В отечественной и зарубежной археологии до недавнего времени были известны лишь некоторые аспекты ремес ленного производства греческих колонистов, освоивших СевероЗападное Причерноморье в конце vii в. до н. э. Так, для античного поселения на ове Березань (Борисфен) наиболее полно изучено металлообрабатывающее ремесло. В то же время раскопки городища давали довольно большой процент находок местного керамического производства.
Результатом археологических исследований последних лет стало раскрытие керамических обжигательных пе чей в слое середины vi в. до н. э. на небольшой территории в центральной части поселения, что позволяет нам сделать предположение о существовании здесь в это время гончарного района.
Некоторые печи были разрушены в результате аварии, сохранив в своем заполнении обжигаемую продукцию. Это — сероглиняные светильники и столовая посуда, являющаяся подражанием керамике Северной Ионии. Only several aspects of handicraft industry of Greek colonists who settled northwestern coast of the Black Sea at the end of the 7th century BC were known in home and foreign literature till recently. For instance, for ancient Greek settlement at Berezan island (Borysthenes), metalworking is the most comprehensively studied craft. at the same time, excavations at the hillfort presented quite high percentage of finds of local ceramic production.
The archaeological research of recent years resulted in the discovery of ceramic firing kilns in the layer dated back to the middle of the 6th century BC at a small area in the central part of the settlement, allowing the author to presume the existence of potter’s district here in this period.
Some kilns perished after the damage having preserved fired products in their feeling. They are grey clay lamps and kitchenware imitating north ionic ceramics.